2014
DOI: 10.1017/s1461145714000959
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of antipsychotics attenuates ongoing and ketamine-induced increases in cortical γ oscillations

Abstract: Noncompetitive N-methyl-d-aspartate receptor (NMDAr) antagonists can elicit many of the symptoms observed in schizophrenia in healthy humans, and induce a behavioural phenotype in animals relevant to psychosis. These compounds also elevate the power and synchrony of gamma (γ) frequency (30-80 Hz) neural oscillations. Acute doses of antipsychotic medications have been shown to reduce ongoing γ power and to inhibit NMDAr antagonist-mediated psychosis-like behaviour in rodents. This study aimed to investigate how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 53 publications
1
30
0
1
Order By: Relevance
“…Because dopamine has an inhibitory effect on cortical activity (Ciccone, 2015), antipsychotics tend to shift the balance of activity towards cortical excitation. There is evidence from preclinical studies that chronic administration of antipsychotics can reduce steady state oscillatory power in the gamma frequency (Anderson et al, 2014), whilst non-invasive neuroimaging has shown enhanced steady state delta and theta but reduced alpha and beta amplitude after administration of antipsychotics in healthy volunteers (Galderisi et al, 1996; Hubl et al, 2001). The observation that taking into account patients' daily dose of psychotropic medication did not alter the results, together with evidence from other studies indicating that oscillatory abnormalities are present in unmedicated patients with schizophrenia (Boutros et al, 2008; Gallinat et al, 2004; Sun et al, 2013) and in first degree relatives (Hong et al, 2012) suggests that the abnormalities observed in our study are unlikely to be attributable to medication.…”
Section: Discussionmentioning
confidence: 99%
“…Because dopamine has an inhibitory effect on cortical activity (Ciccone, 2015), antipsychotics tend to shift the balance of activity towards cortical excitation. There is evidence from preclinical studies that chronic administration of antipsychotics can reduce steady state oscillatory power in the gamma frequency (Anderson et al, 2014), whilst non-invasive neuroimaging has shown enhanced steady state delta and theta but reduced alpha and beta amplitude after administration of antipsychotics in healthy volunteers (Galderisi et al, 1996; Hubl et al, 2001). The observation that taking into account patients' daily dose of psychotropic medication did not alter the results, together with evidence from other studies indicating that oscillatory abnormalities are present in unmedicated patients with schizophrenia (Boutros et al, 2008; Gallinat et al, 2004; Sun et al, 2013) and in first degree relatives (Hong et al, 2012) suggests that the abnormalities observed in our study are unlikely to be attributable to medication.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have studied the effect of individual antipsychotics on gamma power. Sustained and significant decreases in ongoing gamma power were found during chronic administration of haloperidol or clozapine . No study in humans, however, has studied the differing effect of individual antipsychotics on gamma oscillations in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Various animal studies have shown that antipsychotics, both first‐ and second‐generation agents, have been shown to vary spontaneous high‐frequency, especially gamma oscillatory activity . Few studies specifically have investigated antipsychotic treatment effects on human gamma band activity.…”
mentioning
confidence: 99%
“…once daily over 3 days at doses of 3 and 10 mg·kg À1 exhibited efficacy in the formalin assay that was indistinguishable from efficacy responses when these doses were acutely administered. The question of whether longer-term dosing of LY2969822 might lead to tachyphylaxis in rodents was not explored; however, it bears mentioning that the development of tolerance following chronic exposure to mGlu 2/3 receptor agonists in rodents is not consistently observed (see for instance Cartmell et al, 2000b;Schobel et al, 2013;Anderson et al, 2014;Battaglia et al, 2015) and may be a function of several interacting factors including species/strain, assay, dose, route of administration and specific agonist ligand. Importantly, there is no evidence that loss of efficacy on repeat dosing of mGlu 2/3 receptor agonists in rodents translates to humans.…”
Section: Figurementioning
confidence: 99%